Epidemiological Characteristics and Risk Factors of Methamphetamine—Associated Psychotic Symptoms - Su, Meng-Fan; Liu, Mo-Xuan; Li, Jin-Qiao; Lappin, Julia M.; Li, Su-xia; Wu, Ping; Liu, Zhi-Min; Shi, Jie; Lu, Lin; Bao, Yanping (Frontiers in Psychiatry, 2018)
[ABSTRACT] Objective: To explore the epidemiological characteristics and the risk factors for methamphetamine (MA) -associated psychotic symptoms among MA users in China. Methods: A cross-sectional study was conducted between April, 2012 and October, 2015 among individuals for whom MA was the principal drug of use in a Compulsory Drug Detoxification Center in Beijing, Guangdong Province. Demographic, drug use and psychological characteristics were examined using a specifically-designed questionnaire, the Positive and Negative Syndrome Scale, Barratt Impulsive Scale, Hamilton Anxiety Scale and Beck Depression Inventory. Logistic regression was performed to explore the risk factors for MA-associated psychotic symptoms. Results: A total of 1685 participants were included. The group were predominantly aged 30 or above, unemployed, and unmarried Han Chinese men, with limited education. The duration of MA use was more than 3 months in 72.3% of the participants. 47.8% reported that the dose of MA use was greater than or equal to 0.2 g per time. 11.5% had used two or more synthetic drugs. The prevalence of MA-associated psychotic symptomswas 17.0% among MA users during periods of abstinence. Multiple logistic regression analyses showed that a higher dose (≥0.2 g per time), a longer duration of MA use (>3 months) and a history of heroin use, and tobacco use were associated with MA-associated psychotic symptoms, with adjusted odds ratios (ORs) of 1.96 (95% confidence interval [CI]: 1.40-2.76), 1.98 (95% CI: 1.33-2.96) and 2.45 (95% CI: 1.67-3.60), 1.78(95% CI: 1.27-2.49) respectively. MA-associated psychotic symptoms were less common among married/cohabitating than unmarried (OR=0.56; 95% CI: 0.39-0.81), and unemployed than employed (OR=0.65; 95% CI: 0.47-0.92) individuals. MA users with anxiety and depression symptoms had significantly greater risk for MA-associated psychotic symptoms by 9.70(6.92-13.59) and 1.90 (1.36-2.65) times respectively. Individuals with higher impulsivity were more likely to have MA-associated psychotic symptoms than those with lower (OR=2.19; CI:1.50-3.20). Conclusion: MA-associated psychotic symptoms occurred frequently among MA users in China. The efforts that facilitate drug users’ attempts to reduce MA use, abstain from poly-drug use, and to control associated psychiatric symptoms and impulsivity should be supported because of their potential contribution to MA-associated psychotic symptoms in this population.